Private universities in Indonesia: Perspective on students’ satisfaction and marketing strategy in Post Pandemic Era - Luckyardi, Senny; Hurriyati, Ratih; Widjajanta, Bambang; Disman, Disman; Dirgantari, Puspo Dewi; Wibowo, Bagas Dwi Suryo (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
This research aimed to analyse the student’s satisfaction toward e-learning implementation in private universities and how it can be used as a marketing tool in the post-pandemic era. Furthermore, the antecedents of e-learning were also studied. We selected an ICT-based private university in Bandung as a model. The data were collected using e-questionnaire, distributed to students who was subjected to PLS-SEM to be used in the analysis. The results showed that e-learning implementation positively contributed to students’ satisfaction. Additionally, from the perspective of students as consumers, e-learning implementation significantly leads to the increase of their satisfaction which contributes to a good marketing strategy. This study has novel input to enrich the literature of e-learning domain as one of the requirements in creating a digitalized university as a marketing tool for the initiation of digitalized university